STUDI KASUS ANAK BERKEBUTUHAN KHUSUS PENDERITA CHILDHOOD DISENTEGRATIVE DISORDER - Sunaidi; Mamluatun Ni’mah; Magfirotul Hamdiah (Jurnal Bastra (Bahasa dan Sastra), 2024)
This study aims to reveal the phenomena that occur in children with special needs who suffer from Childhood Disentegrative Disorder in the form of spoken language. The symptom of childhood dysentegrative is the occurrence of a decrease in the ability acquired at least the age of two years. Then the ability that has been acquired will decline until the age of three, or four or even ten years. The reality in the field shows that “M” as a respondent has a language disorder in the context of speaking. This research is a qualitative research using a 16-year-old child who has childhood dysentegrative symptoms so that it is said to be a case study research. Data collection techniques used observation, interviews, and documentation, while data analysis techniques used triangulation techniques. The results showed that “M” as a respondent in this study had speech disorders in phoneme replacement, syllable omission, and phoneme omission in spoken morphemes